The Evolution of CRM - Woodcock, Neil; Stone, Merlin (Henry Stewart Talks, 2014)
Characteristics of customer management leaders, Customer management evolution, 21st century CRM, Businesses become socially enabled, The rise and rise of digital, Social and mobile, Spend on social, digital and mobile, UK vs. US, Technology trends, Tablet penetration, B2B, Trends in customer behaviour evolution, Using social to engage, Brand vs. customer mis-alignment, Digital fuels low latency, The B2B lifecycle, Evolving customer behaviour, Spread of information, Community, Discount culture, Listening, CRM challenges, Workflow and agility, Data challenges, Organisational challenges